A synthetic consortium of 100 gut commensals modulates the composition and function in a colon model of the microbiome of elderly subjects. (1st January 2021) - Perez, Marta; Ntemiri, Alexandra; Tan, Huizi; Harris, Hugh M. B.; Roager, Henrik M.; Ribière, Céline; O'Toole, Paul W.
ABSTRACT: Administration of cultured gut isolates holds promise for modulating the altered composition and function of the microbiota in older subjects, and for promoting their health. From among 692 initial isolates, we selected 100 gut commensal strains (MCC100) based on emulating the gut microbiota of healthy subjects, and retaining strain diversity within selected species. MCC100 susceptibility to seven antibiotics was determined, and their genomes were screened for virulence factor, antimicrobial resistance and bacteriocin genes. Supplementation of healthy and frail elderly microbiota types with the MCC100 in an in vitro colon model increased alpha-diversity, raised relative abundance of taxa including Blautia luti, Bacteroides fragilis, and Sutterella wadsworthensis ; and introduced taxa such as Bifidobacterium spp. Microbiota changes correlated with higher levels of branched chain amino acids, which are health-associated in elderly. The study establishes that the MCC100 consortium can modulate older subjects' microbiota composition and associated metabolome in vitro, paving the way for pre-clinical and human trials.